1973
DOI: 10.1002/app.1973.070171102
|View full text |Cite
|
Sign up to set email alerts
|

Melting and crystallization behavior of poly(tetrafluoroethylene). New method for molecular weight measurement of poly(tetrafluoroethylene) using a differential scanning calorimeter

Abstract: synopsisMelting and crystallization behavior of virgin polytetratluoroethylene have been studied using a differential scanning calorimeter. Following quantitative relationship was found between number average molecular weight of polytetrafiuoroethylen_e and the heat of crystallization in the molecular weight range of 5.2X 106 to 4.5XlO': M, = 2.1 X10" AH,-G.16, where a,, is number average molecular weight and AHc is the heat of crystallization in cal/g. The heat of crystallization is independent of cooling rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(65 citation statements)
references
References 1 publication
3
61
0
Order By: Relevance
“…[3,4] Note, that a part of the samples studied in ref. [5,6,25] have a calculated molecular weight,M n , outside the upper limit of Equation (1). That means, those data points are a result of an extrapolation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3,4] Note, that a part of the samples studied in ref. [5,6,25] have a calculated molecular weight,M n , outside the upper limit of Equation (1). That means, those data points are a result of an extrapolation.…”
Section: Resultsmentioning
confidence: 99%
“…Suwa et al [5] investigated in 1973 the heat of crystallisation of PTFE and their correlation to the molecular weight M n using Equation (1). For PTFE with molecular weight M n ranging from 5.2 Á 10 5 to 4.5 Á 10 7 g/mol the following quantitative relationship Summary: The influence of number-average molecular weight M n ranging from 1.4 Á 10 4 to 1.2 Á 10 6 g/mol on the thermal behaviour of polytetrafluoroethylene (PTFE) has been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 between the number-average molecular weight and the heat of crystallization about 7 mg of polymer has been heated with a Perkin Elmer DSC-7 at a rate of 20 K min -1 from room temperature to 650 K. The sample has then been held at this temperature for 5 minutes before cooling with 20 K min -l back to room temperature. Heats of crystallization were obtained from the measured DSC exotherms and the molecular weight was estimated to be 44 x 10 5 gmol-1 , 22 x 10 5 gmol-1 , and 2 x 10 5 gmol-1 for G 163, TFl 750, and KU02, respectively.…”
Section: Experiments Almentioning
confidence: 99%
“…There have been a number of attempts in the past to study the influence of molecular weight on crystallinity and crystallization kinetics. 7- 19 Veda and Nakushima l7 found that the density of poly(ethy1ene terephthalate) is limited by its molecular weight in its extent of increase because of thermal treatments. The higher the molecular weight, the lower is the limiting density after maximum possible crystallization by thermal treatments.…”
Section: Introductionmentioning
confidence: 99%